TINDAK PIDANA PENCURIAN YANG DILAKUKAN PADA SAAT BENCANA KEBAKARAN DI KOTA SAMARINDA - Ismail Ismail (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT The crime of theft committed during the catastrophic fires in cities Samarinda guided by Ony Rosifani, S.H, M.Hum as a mentor I and H. Syamsudin, S.H, M.Hum as a mentor II. Theft problem at the time of the fire disaster is already stipulated in the articles of the criminal code, namely article 363, paragraph 2.Formulation of the problem as follows the factors that led to the crime of theft when a disastrous fire in the city of Samarinda and to know the efforts taken by the police in tackling the crime of theft when a disastrous fire in the city Samarinda.This study was conducted in cities Samarinda precisely in the police office and office BPBD Samarinda city. By taking the data and conduct interviews with the father sat reskrim who handle this case as well the authors also conducted a literature and legislation relating to matters that are discussed in this thesis.The results showed that the background which led to the theft at the time of the fire disaster is caused by several factors, including the economic factors, high levels of unemployment, lack of education a person, as well as environmental factors. And as for the efforts made by the police in tackling criminal offense at the time of the fire disaster that is the way of preventive, curative, and guidance for the public. Suggestions in this study is the police should be more active and people are encouraged to be vigilant to keep belongings from the culprit and do not easily believe with the help of other people who want to help.